Age-specific serum calcium levels in healthy individuals from the Xing’an League: a descriptive study - Haiyan Hu; Wulan Wang; Zenan Chang; Siyu Wang; Yulong Zhang; Lili Zou; Wanying Song; Jing Zhang (Journal of Health, Population and Nutrition)
Abstract Objective To determine the age-specific distribution of serum calcium levels in the Xing’an League population and assess the applicability of current national standards. Methods Data were collected from 3000 healthy individuals across different age groups in the Xing’an League, stratified by sex and age. Serum calcium levels were measured, and statistical methods were used to analyse sex- and age-related differences. The relevance of the current Chinese Health Industry Standard reference intervals for serum calcium was evaluated, and age-related trends were assessed. Results Significant differences in serum calcium levels were found between sexes and across age groups. The current national reference intervals did not adequately capture the age- and region-specific characteristics of serum calcium levels in the Xing’an League population, highlighting the need for localized evaluation criteria. Conclusion The study demonstrates the impact of sex and age on serum calcium levels and emphasises the importance of recognising regional variations. The findings provide a scientific basis for enhancing disease prevention and developing personalised treatment strategies to address regional disparities in clinical practice.